2013
DOI: 10.1038/srep03377
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Auraptenol attenuates vincristine-induced mechanical hyperalgesia through serotonin 5-HT1A receptors

Abstract: Common chemotherapeutic agents such as vincristine often cause neuropathic pain during cancer treatment in patients. Such neuropathic pain is refractory to common analgesics and represents a challenging clinical issue. Angelicae dahuricae radix is an old traditional Chinese medicine with demonstrated analgesic efficacy in humans. However, the active component(s) that attribute to the analgesic action have not been identified. This work described the anti-hyperalgesic effect of one coumarin component, aurapteno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The main components of Angelicae dahuricae radix are reported to be volatile oil and ingredients of coumarin, including imperatorin, isoimperatorin and cnidilin, and these active ingredients of Angelicae dahuricae radix may explain its multiple functions (13). Previous studies have shown that auraptenol, a major coumarin component from Angelicae dahuricae radix, had a robust antinociceptive effect in a chronic neuropathic pain mouse model (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main components of Angelicae dahuricae radix are reported to be volatile oil and ingredients of coumarin, including imperatorin, isoimperatorin and cnidilin, and these active ingredients of Angelicae dahuricae radix may explain its multiple functions (13). Previous studies have shown that auraptenol, a major coumarin component from Angelicae dahuricae radix, had a robust antinociceptive effect in a chronic neuropathic pain mouse model (1).…”
Section: Discussionmentioning
confidence: 99%
“…It has a strong scent, and its leaves are used to make incense (1). Angelicae dahuricae radix is the dried root of Angelica dahurica Bentham et Hooker and Angelica dahurica (Fisch.…”
Section: Introductionmentioning
confidence: 99%
“…The highest dose of auraptenol (0.8 mg/kg, i.p.) totally suppressed the mechanical hyperalgesia without affecting the general locomotor activity [22].…”
Section: Auraptenolmentioning
confidence: 93%
“…treatment. The doses of gabapentin, WAY 100635 and yohimbine were chosen on the basis of previously published results Wang et al, 2013;Vergelli et al, 2015).…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%